Purification and Characterization of Cellulase of Mold Isolated from Vermicomposting Process of Palm Oil Empty Fruit Bunches - Rosita Fitrah Dewi; Kahar Muzakhar (Jurnal Biodjati, 2018)
In previous investigation of vermicomposting process of palm oil empty fruit bunches, five cellulase-producing microorganisms had been isolated. An isolated VTM1 identified as Aspergillus sp. as a cellulase producing mold, and proven produced extracellular cellulase in solid state fermentation of palm oil empty fruit bunches. The obtaining crude cellulase was purified to homogeneity by ammonium sulfate precipitation, gel filtration on Sephadex G-100 chromatography, and finally purified on ion exchange chromatography on DEAE Cellulofine A-500. The yield and purification fold were 12.89% and 107.50, respectively. The purified cellulase was easily released glucose when 5% CMC applied as substrate, as shown by TLC analysis. The purified cellulase had an optimal pH and temperature at 4.0 and 45°C, and was stable at pH 3-7 and 30-50°C, respectively.